Impact of Gouy-Chapman-Stern model on conventional ISFET sensitivity and stability - Ahmed M. Dinar; AS Mohd Zain; F. Salehuddin; M.K. Abdulhameed; Mowafak K. Mohsen; Mothana L. Attiah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Utilizing Gouy-Chapman-Stern model can improve ISFET sensitivity and stability using Stern layer in direct contact with electrolyte in ISFET sensing window. However, this model remains a challenge in mathematical way, unless it’s re-applied using accurate simulation approaches. Here, we developed an approach using a commercial Silvaco TCAD to re-apply Gouy-Chapman-Stern model as ISFET sensing membrane to investigate its impact on sensitivity and stability of conventional ISFET. Sio2 material and high-k Ta2O5 material have been examined based on Gouy-Chapman and Gouy-Chapman-Stern models. Results shows that the ISFET sensitivity of SiO2 sensing membrane is improved from ~38 mV/pH to ~51 mV/pH and the VTH shift stability is also improved. Additionally, the results indicate that the sensitivity of Ta2O5 is 59.03 mV/pH that hit the Nearnst Limit 59.3 mV/pH and achieves good agreements with mathematical model and previous experimental results. In conclusion, this investigation introduces a real validation of previous mathematical models using commercial TCAD approach rather than expensive fabrication that paves the way for further analysis and optimization.